On the significance of craniosynostosis in a case of Kabuki syndrome with a concomitant KMT2D mutation and 3.2 Mbp de novo 10q22.3q23.1 deletion. Issue 8 (7th June 2017) - Topa, Alexandra; Samuelsson, Lena; Lovmar, Lovisa; Stenman, Göran; Kölby, Lars
Abstract : Craniosynostosis has rarely been described in patients with Kabuki syndrome. We report here a boy with facial asymmetry due to combined premature synostosis of the right coronal and sagittal sutures as well as several symptoms reminiscent of Kabuki syndrome (KS). Our case supports previous observations and suggests that craniosynostosis is a part of the KS phenotype. The uniqueness of our case is the sporadic co‐occurrence of two genetic disorders, that is, a de novo frameshift variant in the KMT2D gene and a de novo 3.2 Mbp 10q22.3q23.1 deletion. Our findings emphasize the importance of the initial clinical assessment of children with craniosynostosis and that genomic and monogenic disorders, such as Kabuki syndrome, should be considered among the differential diagnoses of syndromic forms of craniosynostosis.